The effect of administrative processes for unregistered employers on the increase in the number of participants registering at BPJS Ketenagakerjaan / Erindah Dimisyqiyani … [et al.] - Dimisyqiyani, Erindah; Sujoko, Dyah Suryaning; Amaliyah, Amaliyah; Apriliani, Lydia; Yuliawan, Rahmat (2023)
This study aims to determine the effect of Administrative Processes for Unregistered Employers in Bahasa Indonesia is Proses Administrasi Pemberi Kerja Wajib Belum Daftar (PWBD) on increasing the number of participants registering at BPJS Ketenagakerjaan. The research method used is quantitative descriptive through analysis of classical assumption tests, hypothesis testing, and coefficient of determination tests. The test determines how much influence the independent variables have on the dependent variable. Based on the results of the analysis, simultaneously, the entire PWBD administration process has a significant effect on increasing the number of participants registering at BPJS Ketenagakerjaan with a determination coefficient of 47.6%. The limitations of this research problem are the administrative process of BPJS Ketenagakerjaan PWBD for PKBU small-scale subsidiary companies in Surabaya starting from 2021 – 2023 and listed in the cleansing data of BPJS Ketenagakerjaan, Karimun Jawa Surabaya branch. This study suggests that to achieve the membership target, BPJS Ketenagakerjaan must continue to carry out PWBD administration, innovate the PWBD administration process, and maintain good relations between employees. Other marketing mixes can be used in programs to increase the number of participants registering at BPJS Ketenagakerjaan.